Ca2+-induced self-assembly of Bombyx mori silk sericin into a nanofibrous network-like protein matrix for directing controlled nucleation of hydroxylapatite nano-needles. Issue 12 (17th February 2015) - Yang, Mingying; Zhou, Guanshan; Shuai, Yajun; Wang, Jie; Zhu, Liangjun; Mao, Chuanbin
Abstract : Ca 2+ binding induces self-assembly of sericin into a nanofibrous network and the subsequent mineralization for promoting osteogenic differentiation of BMSCs. Abstract : Bone biomineralization is a well-regulated protein-mediated process where hydroxylapatite (HAP) crystals are nucleated with preferred orientation within the self-assembled protein matrix. Mimicking this process is a promising approach to the production of bone-like protein/mineral nanocomposites for bone repair and regeneration. Towards the goal of fabricating such nanocomposites from sericin, a protein spun by Bombyx mori ( B. mori ) silkworm, and bone mineral HAP, for the first time we investigated the chemical mechanism underpinning the synergistic processes of the conformational change/self-assembly of B. mori sericin (BS ) as well as the nucleation of HAP on the resultant self-assembledBS matrix. We found thatBS, rich in anionic amino acid residues, could bind Ca 2+ ions from the HAP precursor solution through electrostatic attraction. The Ca 2+ binding drove the conformational change ofBS from random coils into β-sheets and its concomitant self-assembly into the interconnected nanofibrous network-like protein matrix, which initiated the nucleation and growth of HAP crystals. HAP crystals directed by the resultant self-assembledBS matrix grew preferentially along their crystallographic c -axis, leading to the formation of HAP nano-needles. The HAP nano-needles in the self-assembledBS matrix were subsequently aggregated into globules, probably driven by the hydrogen bonding between CO groups ofBS and O–H groups of HAP nano-needles. The present work sheds light on the chemical mechanisms ofBS self-assembly and the controlled mineralization directed by the self-assembled matrix. We also found that the resultant nanocomposites could promote the osteogenic differentiation of human bone marrow-derived mesenchymal stem cells. Thus our work also generates a biomimetic approach to bone-like silk protein/mineral nanocomposite scaffolds that can find potential applications in bone repair and regeneration.